CHARACTERISTICS OF DIABETIC NEPHROPATHY IN PATIENTS WITH DIABETES MELLITUS (International Conference on Medical Science, Medicine and Public Health, 2025)
To study the occurrence and characteristics of diabetic nephropathy in patients with diabetes mellitus.